Nilai Tukar Subsisten Dan Kesejahteraan Petani Kelapa di Desa Teluk Ketapang Kecamatan Senyerang Kabupaten Tanjung Jabung Barat - Nida Kemala; Kholik Maulana (Jurnal MeA (Media Agribisnis), 2023)
This study was carried out in Teluk Ketapang Village, Senyerang District, Tanjung Jabung Barat. It  used a survey method which the number of samples taken  were 37 farmers. The aimed of this reseach were  to describe the  coconut farming, to analyze the subsistence exchange rate of the  and to know the welfare of coconut.  This study informed that the planting was done   of 9x9x9 meters as a distance . Farmers applied  fertilization (NPK and Urea) and sprayed with herbicides ( gramaxone and round-up), The collecting coconut products were sold to middlemens. The Subsistence Exchange Rate was 0.70 (0.70 < 1), and  it means that the revenue of coconut farming was not enough to meet the total expenditure costs of the farmers (both for input of coconut farming and consumtion expenditure).  So it can be classified as unwelfare.